Going through the lockdown: a longitudinal study on the psychological consequences of the coronavirus pandemic - Salvatore Gullo; Ilaria Misici; Arianna Teti; Michele Liuzzi; Enrico Chiara (Research in Psychotherapy, 2021)
Coronavirus 2019 pandemic lockdown in Italy lasted for 2 months, 1 week and 2 days. During this long period, one of the longest in Europe, the restrictions produced effects on people’s psychological well-being, with consequences that also continued after lockdown. The purpose of the study is to investigate these effects and how they changed in the general population over a period of time. We are also interested in exploring people’s post-lockdown anxiety and concerns. We conducted an online survey using snowball sampling techniques. The longitudinal study consisted of four administrations covering a period of 10 weeks between April (baseline) and June (last follow-up). Levels of anxiety and depression were assessed by GAD-7 and PHQ-9, coping strategies were assessed by Brief Resilient Coping Scale (BRCS) and social support was assessed by MSPSS. Post-lockdown anxiety was explored by developing a set of ad-hoc questions. PCA was used to determine the principal categories of post-lockdown anxiety/concern resulting from the ad-hoc questions. Longitudinal data, given their nested structure, were analyzed through mixed modeling. Of the 411 responders at baseline, 169 had at least 3 out of 4 data points; the analysis was therefore conducted on this sample. Levels of depression and anxiety were found to be significantly higher in the study sample in comparison with normative samples for each of the fourtime points; levels of coping showed that scores from the study sample were significantly lower than normative data at all-time points. Levels of perceived social support were significantly lower than normative data at the baseline and the first follow-up. The results of the study suggest that the lockdown experience had enduring consequences on the mental health of individuals. Prevention and support interventions to limit the psychological distress caused by COVID-19 should be taken into consideration in countries experiencing a second wave of the pandemic.